2018
DOI: 10.1016/j.cell.2018.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Co-optation of Tandem DNA Repeats for the Maintenance of Mesenchymal Identity

Abstract: Tandem repeats (TRs) are generated by DNA replication errors and retain a high level of instability, which in principle would make them unsuitable for integration into gene regulatory networks. However, the appearance of DNA sequence motifs recognized by transcription factors may turn TRs into functional cis-regulatory elements, thus favoring their stabilization in genomes. Here, we show that, in human cells, the transcriptional repressor ZEB1, which promotes the maintenance of mesenchymal features largely by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 78 publications
2
30
0
Order By: Relevance
“…In the context of an effort to determine how the transcriptional networks operating in exocrine pancreas are rewired in PDACs (Diaferia et al, 2016;Balestrieri et al, 2018), we report here that while FOXA1 and FOXA2 are co-expressed in well-differentiated PDAC cells, they are dissociated in the less differentiated cellular component, in which only FOXA2 is expressed, albeit nonuniformly. This dissociation is reminiscent of normal embryonic development, in which FOXA2 is expressed before FOXA1 (Sasaki & Hogan, 1993), thus explaining the inability of the latter to ◀ Figure 6.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the context of an effort to determine how the transcriptional networks operating in exocrine pancreas are rewired in PDACs (Diaferia et al, 2016;Balestrieri et al, 2018), we report here that while FOXA1 and FOXA2 are co-expressed in well-differentiated PDAC cells, they are dissociated in the less differentiated cellular component, in which only FOXA2 is expressed, albeit nonuniformly. This dissociation is reminiscent of normal embryonic development, in which FOXA2 is expressed before FOXA1 (Sasaki & Hogan, 1993), thus explaining the inability of the latter to ◀ Figure 6.…”
Section: Discussionmentioning
confidence: 94%
“…ChIP-seq was carried out using previously described protocols (Curina et al, 2017;Balestrieri et al, 2018) on an Illumina HiSeq 2000 platform. 10 6 (H3K27ac) or 50-150 × 10 6 (TFs) were either fixed with formaldehyde as described before (for H3K27ac, FOXA2, HOXB8, and JUNB ChIP-seq) or fixed with a double cross-linking protocol (for FOS ChIP-seq).…”
Section: Chip-seqmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that two enhancers in the mouse genome exhibit an exceptional density of PU.1 motifs, which are triggers for outlier levels of TRIM33 recruitment to cause repression of neighboring genes Bim and Atp1b3 (Wang et al, 2015a). In a recent study, it was found that DNA replication errors can produce tandem repeats to produce homotypic TF binding sites, which can promote the evolution of novel cis -regulatory elements (Balestrieri et al, 2018). Based on these findings, we propose that homotypic motif clustering as a general mechanism by which transcription factors and cofactors become endowed with high-precision regulatory functions during evolution.…”
Section: Discussionmentioning
confidence: 99%